Update on the effects of microgravity on the musculoskeletal system - Otto J. Juhl (Nature Portfolio, 2021)
Abstract With the reignited push for manned spaceflight and the development of companies focused on commercializing spaceflight, increased human ventures into space are inevitable. However, this venture would not be without risk. The lower gravitational force, known as microgravity, that would be experienced during spaceflight significantly disrupts many physiological systems. One of the most notably affected systems is the musculoskeletal system, where exposure to microgravity causes both bone and skeletal muscle loss, both of which have significant clinical implications. In this review, we focus on recent advancements in our understanding of how exposure to microgravity affects the musculoskeletal system. We will focus on the catabolic effects microgravity exposure has on both bone and skeletal muscle cells, as well as their respective progenitor stem cells. Additionally, we report on the mechanisms that underlie bone and muscle tissue loss resulting from exposure to microgravity and then discuss current countermeasures being evaluated. We reveal the gaps in the current knowledge and expound upon how current research is filling these gaps while also identifying new avenues of study as we continue to pursue manned spaceflight.